Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1002/ijch.199900033
|View full text |Cite
|
Sign up to set email alerts
|

Covalent and Ionic States of Strong Acids at the Ice Surface

Abstract: The relationship between the degree of ionization and the environment of a strong acid is of basic scientific interest. Often this relationship reduces to the interdependence of iodacid hydration and proton transfer. Despite the presence of pure water, the surface of crystalline ice, particularly at cryogenic temperatures, is one of limited (controlled?) availability of water of hydration. Here, the detailed nature of the ice surface and the states of strong acids adsorbed to ice at cryogenic temperatures are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
45
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 44 publications
5
45
0
Order By: Relevance
“…This broad absorption is ubiquitous in the vibrational spectroscopy of aqueous acid solutions and is thus broadly recognized as the spectroscopic hallmark of the aqueous proton. The presence of aqueous protons suggests that most (some) HNO 3 molecules have dissociated in the 5–15% (20–60%) HNO 3 mole fraction cryogenic nitric acid solutions even at temperatures as low as 45 K, a significantly lower temperature than those of previous spectroscopic studies. , …”
Section: Resultsmentioning
confidence: 89%
“…This broad absorption is ubiquitous in the vibrational spectroscopy of aqueous acid solutions and is thus broadly recognized as the spectroscopic hallmark of the aqueous proton. The presence of aqueous protons suggests that most (some) HNO 3 molecules have dissociated in the 5–15% (20–60%) HNO 3 mole fraction cryogenic nitric acid solutions even at temperatures as low as 45 K, a significantly lower temperature than those of previous spectroscopic studies. , …”
Section: Resultsmentioning
confidence: 89%
“…Investigating the chemical state of HNO 3 at the surface of supercooled solutions or ice therefore requires surface-sensitive spectroscopic tools and/or appropriate sample preparation methods. Only by reaching cryogenic temperatures (i.e., in the 70−135 K range by Devlin et al 14 and the 130−150 K range by Pursell et al 13 ) has molecular nitric acid been observed at the surface of ice. Unfortunately, both studies relied on FTIR spectroscopy, which lacks the surface specificity and sensitivity to detect submonolayer coverages of HNO 3 adsorbed onto ice.…”
mentioning
confidence: 99%
“…Accordingly, their sample preparation methodology and their experimental conditions suggest that they observed molecular nitric acid as a result of multilayer condensation 13 or in the form of nitric acid nanocrystals at the surface of ice. 14 Recently, Krepelova et al 35 used near-edge X-ray absorption fine structure (NEXAFS) to study the adsorption of HNO 3 onto ice at 230 K, relying, however, on heterogeneous NO 2 hydrolysis as a source of HNO 3 . They reported the observation of nitrates dissolved within a 1.1 nm thick supercooled nitric acid solution layer at the ice surface, but they could not observe molecular HNO 3 under these conditions.…”
mentioning
confidence: 99%
See 2 more Smart Citations